A Process & Impact Evaluation of the Veterans Moving Forward: Best Practices, Outcomes, and Cost-Effectiveness, United States, 2015-2016 - Burke, Cynthia ([Verlag nicht ermittelbar], 2020)
In 2014, the San Diego Association of Governments applied for and received funding from the National Institute of Justice (NIJ) to conduct a process and impact evaluation of the Veterans Moving Forward (VMF) program that was created by the San Diego County Sheriff's Department in partnership with the San Diego Veterans Administration (VA) in 2013. VMF is a veteran-only housing unit for male inmates who have served in the U.S. military. When the grant was written, experts in the field had noted that the population of veterans returning to the U.S. with numerous mental health issues, including post-traumatic stress disorder (PTSD), traumatic brain injury (TBI), and depression, were increasing and as a result, the number of veterans incarcerated in jails and prisons was also expected to increase. While numerous specialized courts for veterans had been implemented across the country at the time, veteran-specific housing units for those already sentenced to serve time in custody were rarer and no evaluations of these units had been published. Since this evaluation grant was awarded, the number of veteran-only housing units has increased, demonstrating the need for more evaluation information regarding lessons learned. A core goal when creating VMF was to structure an environment for veterans to draw upon the positive aspects of their shared military culture, create a safe place for healing and rehabilitation, and foster positive peer connections. There are several components that separate VMF from traditional housing with the general population that relate to the overall environment, the rehabilitative focus, and initiation of reentry planning as early as possible. These components include the selection of correctional staff with military backgrounds and an emphasis on building on their shared experience and connecting through it; a less restrictive and more welcoming environment that includes murals on the walls and open doors; no segregation of inmates by race/ethnicity; incentives including extended dayroom time and use of a microwave and coffee machine (under supervision); mandatory rehabilitative programming that focuses on criminogenic and other underlying risks and needs or that are quality of life focused, such as yoga, meditation, and art; a VMF Counselor who is located in the unit to provide one-on-one services to clients, as well as provide overall program management on a day-to-day basis; the regular availability of VA staff in the unit, including linkages to staff knowledgeable about benefits and other resources available upon reentry; and the guidance and assistance of a multi-disciplinary team (MDT) to support reentry transition for individuals needing additional assistance. The general criteria for housing in this veteran module includes: (1) not being at a classification level above a four, which requires a maximum level of custody; (2) not having less than 30 days to serve in custody; (3) no state or federal prison holds and/or prison commitments; (4) no fugitive holds; (5) no prior admittance to the psychiatric security unit or a current psychiatric hold; (6) not currently a Post-Release Community Supervision Offender serving a term of flash incarceration; (7) not in custody for a sex-related crime or requirement to register per Penal Code 290; (8) no specialized housing requirements including protective custody, administration segregation, or medical segregation; and (9) no known significant disciplinary incidents.